2014
DOI: 10.1007/s10450-014-9630-z
|View full text |Cite
|
Sign up to set email alerts
|

CO2 sorption in wet ordered mesoporous silica kit-6: effects of water content and mechanism on enhanced sorption capacity

Abstract: The sorption isotherms of CO 2 in wet ordered mesoporous silica KIT-6 with different amounts of pre-adsorbed water were firstly collected experimentally using a volumetric method in the temperature range of 275-281 K. The isotherms show an inflection point indicating CO 2 hydrates form in the pore spaces which is proofed by the enthalpy change calculated at the inflection pressure, and the quantity of water content shows considerable effect on the sorption capacity of CO 2 . The highest enhancement of sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 21 publications
7
40
0
3
Order By: Relevance
“…CCS is important to mitigate the global warming and its consequences by capture of CO 2 from large anthropogenic sources. Aqueous alkanolamines and chilled ammonia based absorption process [5,6], membrane separation process [7,8], novel cryogenic process [9], algal biomass process [10,11] and porous solid adsorption process [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are most commonly used for CO 2 capture. Among these processes aqueous alkanolamine especially monoethanolamine (MEA) and diethanolamine (DEA) based absorption process is well known with significant commercial application for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…CCS is important to mitigate the global warming and its consequences by capture of CO 2 from large anthropogenic sources. Aqueous alkanolamines and chilled ammonia based absorption process [5,6], membrane separation process [7,8], novel cryogenic process [9], algal biomass process [10,11] and porous solid adsorption process [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] are most commonly used for CO 2 capture. Among these processes aqueous alkanolamine especially monoethanolamine (MEA) and diethanolamine (DEA) based absorption process is well known with significant commercial application for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…Since each isotherm starts at a pressure reading of zero, it is necessary to place the system in a vacuum [17]. Thus, the wet sample was cooled to -20°C for 4 h to minimize the loss of water due to vaporization [18]. Then, the temperature of the chamber was raised to the specified value before sorption measurement was started [5].…”
Section: Experimental Workmentioning
confidence: 99%
“…1, it can be observed that the hydrate is started to form at pressure around 25 bar for curves 4 and the hydrate formation pressure increases for curves 2 and 3. The phenomenon may due to insufficient amount of pre-adsorbed water to trap CO 2 molecules for formation of CO 2 hydrate in which only the smaller pores are firstly filled with water [18]. When hydrate is formed in small pores, very high excess Gibbs free energies is produced on the surface and required higher formation pressure [18].…”
Section: Co2 Sorption On Wet Cao At 2°cmentioning
confidence: 99%
See 1 more Smart Citation
“…They have gained attention in recent years [3] as the concentration of CO2 increases from 278 ppm to about 405 ppm from 1970 to 2017 as measured by Global Monitoring Division of NOAA/Earth System Research Laboratory [4]. Various CO2 removal methods such as absorption [5][6][7], membrane separation [8,9], cryogenic distillation [10] and adsorption [11][12][13][14][15] have been developed. Among these techniques, an adsorption technique received great attention due to its highly energy efficient and several other competitive advantages [3,16,17].…”
Section: Introductionmentioning
confidence: 99%